2015
DOI: 10.1111/bjh.13778
|View full text |Cite
|
Sign up to set email alerts
|

The human Kell blood group binds the erythroid 4.1R protein: new insights into the 4.1R-dependent red cell membrane complex

Abstract: Summary Protein 4.1R plays an important role in maintaining the mechanical properties of the erythrocyte membrane. We analysed the expression of Kell blood group protein in erythrocytes from a patient with hereditary elliptocytosis associated with complete 4.1R deficiency (4.1(−) HE). Flow cytometry and Western blot analyses revealed a severe reduction of Kell. In vitro pull down and co-immunoprecipitation experiments from erythrocyte membranes showed a direct interaction between Kell and 4.1R. Using different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…PKA is essential for heme biosynthesis in the process of erythropoiesis 21 . Xk encodes a component of red blood cell membrane complex, which might relate to membrane reorganization of erythrocyte 22 . These previous studies support the idea that Akap7 and Xk genes play important roles in erythroblast differentiation (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PKA is essential for heme biosynthesis in the process of erythropoiesis 21 . Xk encodes a component of red blood cell membrane complex, which might relate to membrane reorganization of erythrocyte 22 . These previous studies support the idea that Akap7 and Xk genes play important roles in erythroblast differentiation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Akap7 might be also important for erythroid differentiation as a PKA scaffold. The other suggested target, Xk encodes a protein which has been reported to be a component of a multiprotein complex involved in erythrocyte membrane and cytoskeleton interaction 22 . Xk deficiency leads to McLeod syndrome, which has been reported to be accompanied with morphological and functional damages of red blood cells 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Such a structured membrane is also requested to support the biophysical requirements for invasion, establishing the correct tension for the DBP-DARC tight junction and, potentially, of unidentified receptor/ligand interactions, to efficiently interact (Kariuki et al, 2020). DARC expression dependency on the junctional complex with protein 4.1 supports this fact, as protein 4.1 deficiency reduces the expression of DARC (Salomao et al, 2008;Azouzi et al, 2015). The gradual remodeling of the reticulocyte membrane's nanostructure (Li et al, 2018), involving the loss of up to one-third of its surface area (Griffiths et al, 2012), has been widely studied with the use of a variety of approaches, such as SEM, TEM, micropipette aspiration, and atomic force microscopy (Malleret et al, 2013;Malleret et al, 2015).…”
Section: A Constant Remodeling Of the Reticulocyte Membrane In Vitro mentioning
confidence: 99%
“…4.1R is a key membrane skeletal protein in erythrocytes, which contain a highly conserved region known as the FERM domain [36,37] that binds membrane proteins and lipids. It has been reported that 4.1R acts as a linker between the actin cytoskeleton and components of tight junctions and adherens junctions [37,38] and is involved in cell volume regulation and cell morphology [39]. Herein, we found that 4.1R overexpression provided longer OS and RFS in all BC patients and it also showed better prognosis in ER-positive and ER-negative subtypes BC patients according to subgroup analysis, as was also found in basal and luminal B subtypes BC patients.…”
Section: Discussionmentioning
confidence: 99%